Intrinsic Fluorescence as a Spectral Probe for Protein Denaturation Studies in the Presence of Honey - Wong, Y.H.; Kadir, H.A.; Tayyab, S. (Kluwer (now part of Springer), 2015)
Honey was found to quench the intrinsic fluorescence of bovine serum albumin (BSA) in a concentration dependent manner, showing complete quenching in the presence of 5% (w/v) honey. Increasing the protein concentration up to 5.0 μM did not lead to the recovery of the protein fluorescence. Urea denaturation of BSA, which otherwise shows a two-step, three-state transition, using intrinsic fluorescence of the protein as the probe failed to produce any result in the presence of 5% (w/v) honey. Thus, intrinsic fluorescence cannot be used as a spectral probe for protein denaturation studies in the presence of honey.